Clinical Characteristics of Patients with Cancer Presenting to the Emergency Department and Their Use of Emergency Medical Service Transport. (1st November 2020) - Chen, Baibing; Kanaan, Christopher; Jaiyesimi, Ishmael; Ezekwudo, Daniel; Swor, Robert
Abstract: Objectives: Although life-threatening emergencies for cancer patients are relatively rare, cancer patients often seek care in the emergency department. The use of emergency medical service (EMS) by these patients is not well studied. The aim of this study was to investigate the characteristics of cancer patients who present to the emergency department (ED) for care and compare characteristics of patients transported by EMS vs. those transported by private vehicle. Methods : Our retrospective cohort study was conducted in an EMS system with 21, 070 annual transports and an academic ED with 129, 263 annual visits. Our study consisted of patients with a new diagnosis of cancer between January 1 and July 1, 2015 who subsequently presented to the ED between January 1, 2015 and July 1, 2017. Study variables included patient demographics, mode of ED arrival, cancer type and treatment, patient clinical characteristics, and disposition. To describe differences in patient characteristics of EMS vs. private vehicle transport, we report variable frequencies and stratified them by mode of transport. Results: Of the 2, 727 patients with a new diagnosis of cancer, 1, 303 (47.8%) presented to the ED with a total of 3, 590 visits in 30 months. EMS transported 22% of cancer patients to the ED vs. 78% transported by private vehicle. Thus, cancer patients would make up approximately 1.5% (781/52, 675) of all EMS transports during the study period. For those transported by EMS, the most common chief complaints were respiratory distress (16.0%), pain (15.4%), and neurological symptoms (12.6%). Patients with cancer of the lung/respiratory tract (21.5%), upper GI (12.4%), and central nervous system (CNS) (11.0%) were most frequently transported by EMS. Older age, presence of CNS cancer, presentation with neurological or cardiovascular complaints, and higher acuity were significantly associated with EMS transport to ED, while gender and pain severity were not. Patients transported by EMS were more likely to be hospitalized and for greater than 2 days ( p < 0.0001). Conclusions: Cancer patients frequently seek emergency care after initial diagnosis, most commonly present for symptom relief, and are often admitted. Patients transported by EMS are more likely to be admitted and for longer periods of time.